Matrix Transformations and Invariant Mean - Al-Mestady , Mohammed O (Journal of King Abdulaziz University. Science, 2012)
Raimi [R. A. Raimi, Invariant means and invariant matrix methods of summability, Doke. Math. J.30 (1963), 81-94] gave a generalization of almost convergent and named it σ−convergent. In this paper we characterize the matrix classes (I (p, u), V∞) and (I (p, u) Vσ) . (2000) Mathematics Subject Classification : 40C05 ; 40H05. في عام 1963 أعطى ر. أ. ريمي في بحثه "طرق التجميع للمتوسطات الثابتة و المصفوفات الثابتة" تعميما للتقارب التقريبي و سماه تقارب سيجما و في هذا البحث قمنا بإعطاء وصف لصنفين من المصفوفات هما (λ (π ; υ); ς),(λ (π ; υ); ς ∞).